Analysis Of Judicial Policy In Deciding Criminal Acts Based Alternative Indictment (Case Study Decision Number 82 / Pid.B / 2019 / PN.Blora) - Nur Dwi Edie W; Gunarto Gunarto (Jurnal Daulat Hukum, 2020)
In the criminal justice system process the judge plays a role in implementing the decision in which the decision was taken in consideration of the indictments by the prosecutors. In alternative indictments each indictment is mutually exclusive. The judge will choose one of the charges proven according to his conviction. Therefore the alternative indictment is also called the indictment of choice (keuze telastelgging). This research formed the formulation of the problem namely how is the juridical implication of alternative forms of indictment in case number 82 / Pid.B / 2019 / PN.Blora and what is the basis of the judge's judgment in deciding case Number 82 / Pid.B / 2019 / PN.Blora with alternative indictment. This research uses juridical sociological methods with descriptive analysis research specifications. The data used for this study are secondary data with field observation methods and literature and document studies. Based on the research it was concluded (1) the preparation of the indictment in the case of verdict number 82 / Pid.B / 2019 / PN Bla based on Article 378 of the Criminal Code, with an alternative Article 372 of the Criminal Code. In this case, the element that eliminates one another is about the "existence" of the goods in the possession of the defendant. (2) In decision number 82 / Pid.B / 2019 / PN Bla, the judge considers that based on the legal facts revealed in the trial the defendant violated the criminal provisions as in the Second Indictment of alternative charges Article 378 of the Criminal Code Jo Article 64 paragraph 1 of the Criminal Code. Keywords: Judge Policy; Criminal Decisions; Alternative Indictments.